Dopaminergic connectivity reconfiguration in the dementia with Lewy bodies continuum. (March 2023) - Caminiti, Silvia Paola; Pilotto, Andrea; Premi, Enrico; Galli, Alice; Ferrari, Elisabetta; Gipponi, Stefano; Cottini, Elisabetta; Paghera, Barbara; Perani, Daniela; Padovani, Alessandro
Abstract: Introduction: The impairment of nigrostriatal dopaminergic network is a core feature of dementia with Lewy bodies (DLB). The involvement and reconfiguration of extranigrostriatal dopaminergic circuitries in the DLB continuum is still theme of debate. We aim to investigate in vivo the dynamic changes of local and long-distance dopaminergic networks across DLB continuum. Methods: Forty-nine patients (including 29 with dementia and 20 prodromal cases) and fifty-two controls entered the study. Each subject underwent a standardized clinical and neurological examination and performed Brain SPECT to measuring brain dopamine transporter (DAT) density. Spatially normalized images underwent the occipital-adjusted specific binding to obtain parametric data. The ANCOVA was applied to assess 123 I-FP-CIT differences between pDLB, overt-DLB and CG, considering age, gender, and motor impairment as variables of no interest. Between-nodes correlation analysis measured molecular connectivity within the ventral and dorsal dopaminergic networks. Results: Prodromal DLB and DLB patients showed comparable nigrostriatal deficits in basal ganglia regions compared with CG. Molecular connectivity analyses revealed extensive connectivity losses, more in ventral than in dorsal dopaminergic network in DLB dementia. Conversely, the prodromal group showed increased connectivity compared to CG, mostly putamen-thalamus-cortical and striatal-cortical connectivity. Conclusions: This study indicates a comparable basal ganglia deficit in nigrostriatal projections in DLB continuum and supports a different reorganization of extra-striatal dopaminergic connectivity in the prodromal phases of DLB. The shift from an increased to a decreased bilateral putamen-thalamus-cortex connectivity might be a hallmark of transition from prodromal to dementia DLB stages. Highlights: To assess the dynamic local and molecular connectivity changes across the DLB course. Univariate analysis revealed similar DAT derangements in the two groups. Multivariate connectivity approach showed substantial differences between the two groups. Hyperconnectivity in dorsal and ventral dopaminergic networks characterized pDLB. Whereas a widespread loss of connectivity was prominent in overt DLB.